Electrocatalytic performance of commercial vanadium carbide for oxygen reduction reaction. (23rd February 2016) - Yu, Jiemei; Gao, Xueping; Chen, Guozhu; Yuan, Xianxia
Abstract: Transitional metal carbides have great potential to overcome the shortcomings of high-cost and rare sources of precious metal based catalysts. In this paper, we report the catalytic performances of commercial vanadium carbide (VC) and the influences of nitrogen doping on its catalytic performance towards oxygen reduction reactions. Results showed that nitrogen has been doped into the crystal lattice of commercial VC with a slight increase of crystalline size. The half-wave potential of oxygen reduction of the commercial VC and nitrogen doped VC was only 0.06 V and 0.04 V lower than that of Pt/C catalyst, respectively. The stability of VC for catalyzing oxygen reduction could be improved by nitrogen doping. Graphical abstract: Highlights: The catalytic performance of low cost commercial VC is investigated. The work points a new way to develop transitional metal based non-noble catalyst. Nitrogen doping to VC increases the ORR potential.